FRP 보강적층판의 접착성능 및 파괴인성평가 - 정홍주; Hong Ju Jung; 홍순일; Soon Il Hong (목재공학, 2015)
목구조물 접합부에 기존의 슬릿(slit)형 강판을 대체하기 위해서 FRP (Fiber Reinforced Plastic) 보강적층판을 제작하였다. 보강재, 접착제 종류에 따라 총 4가지 타입의 FRP 보강적층판을 제작하였으며, 접합부 적용 전 KSF 3021과 KSF 2160에 의거한 박리실험과 ASTM D5045-99에서 제안한 Compact Tension (CT)형 파괴인성 시험을 실시하였다. 접착성능 시험결과 GFRP textile, GFRP sheet, GFRP Textile-Sheet 타입의 FRP 보강적층판은 침지 및 내수침지박리 시험에서 모두 KS 기준인 박리율 5% 이하를 만족하였다. 그러나 Aramid 타입의 시험편은 침지박리율 4.8%로 기준을 만족하였으나 내수침지박리율 70%로 합격기준을 만족하지 못하였다. 파괴인성 시험결과 단판만을 교차적층 시킨 대조군시험편보다 목재 대비 보강재 체적비를 23%로 함으로서 FRP 보강적층판의 내력이 2∼4배 증가하였다. 그중에서도 GFRP Textile-Sheet 타입의 시험편이 하중 평행방향의 유리섬유 배열로 인해 할렬파단을 억제하면서 대조군 대비응력확대계수 비가 61% 증가되어 파괴를 가장 크게 억제하는 것으로 확인되었다. FRP 보강적층판과 비금속 dowels을 사용한 접합부의 인장형 전단내력은 금속접합에 비해 약 12% 낮은 내력이 측정되었다. In order to replace existing slit type steel plate on the wooden structure joint, the FRP-reinforced laminated plates were produced. Four types of FRP-reinforced laminated plates were produced according to the type of reinforcement and adhesive, and before applying to the joint, the adhesion performance test according to KSF 3021 and KSF 2160 and the Compact Tension (CT) type fracture toughness test specified in ASTM D5045-99 were carried out. As a result of adhesion performance test, all GFRP textile, GFRP sheet, and GFRP Textile-Sheet type FRP-reinforced laminated plates satisfied the requirement of soaking delamination percentage with smaller than 5% based on KS standard. However, aramid type specimen satisfied the standard as the soaking delamination percentage of 4.8% but it did not satisfied the standard as the water proof soaking delamination percentage of 70%. As a result of fracture toughness test, the volume ratio of reinforcement to timber became 23% so that the strength of FRP-reinforced laminated plates increased by two to four times in comparison to the control specimen. It was confirmed that the GFRP Textile-Sheet type specimen was most resistant to the fracture most since the ratio of stress intensity factor compared with that of the control increased to 61% owing to the parallel arrangement of glass fiber to the load. As a result of tensile shear strength test using FRP-reinforced laminated plates and nonmetal dowels, it is about 12% lower than metal connectors.